Mycorrhizal nutrient acquisition strategies shape tree competition and coexistence dynamics. (1st December 2022) - Van Nuland, Michael E.; Ke, Po‐Ju; Wan, Joe; Peay, Kabir G.
Abstract: Mycorrhizal fungi with different nutrient acquisition strategies influence plant species performance and physiology, thereby defining their trophic niche. This might drive resource competition dynamics that cumulatively impact tree species coexistence, but few manipulative experiments have directly tested this. Combining surveys and experiments in a modern coexistence theory framework, we tested how variation in mycorrhizal strategies and nutrient conditions affects plant competitive outcomes. We focused on two genera of co‐occurring tree species with different mycorrhizal states: Acer (arbuscular mycorrhizal, AM) and Populus (dual mycorrhizal, but often considered predominantly ectomycorrhizal, EM). The EM and AM fungal responsiveness in Populus species varied with latitude and nitrogen (N) limitation. Host‐specific soil microbiome conditioning and inorganic N fertilization combined to qualitatively affect coexistence outcomes. Lower N conditions favoured Populus over Acer trees, and N fertilization reversed this outcome for southern species, aligning with regional‐scale forest mycorrhizal transitions. Results from the coexistence experiment also predict competitive exclusion between the tree species pairs, which could arise, in part, from their mycorrhizal differences and is consistent with alternative stable states in dominant forest mycorrhizal strategies. Such bistability appears in natural systems as a bimodal distribution of Populus vs. Acer tree species dominance using long‐term forest inventory data. Synthesis : The magnitude and outcome of microbially mediated competition between Populus and Acer depends on soil nutrient availability, which likely relates to their mycorrhizal differentiation. These findings support the importance of mycorrhizal symbioses for contributing to large‐scale biogeographical patterns of tree species trophic niche separation across soil resource gradients and bistability in forest mycorrhizal structure. Abstract : Mycorrhizal fungi with different nutrient acquisition strategies influence plant species performance and physiology, which ultimately might determine competition and coexistence dynamics. We find that microbially mediated competition between Populus and Acer tree species depends on soil nutrient availability, likely related to their different mycorrhizal associations. These findings support the importance of mycorrhizal symbioses for contributing to large‐scale patterns of tree species distributions and forest mycorrhizal structure.